Wet‐Transfer of Freestanding Dense Colloidal Quantum Dot Films and Their Photonic Device Application. Issue 3 (27th December 2017) - Han, Changhyun; Jung, Hyunho; Lee, Jongho; Lee, Myungjae; Park, Yeonsang; Cho, Kyung‐Sang; Jeon, Heonsu
Abstract: A method of wet‐transferring a densely packed colloidal quantum dot (CQD) film is reported herein. Layers of poly(vinyl alcohol) (sacrificial layer) and poly(methyl methacrylate) (temporary mechanical support) are spin‐coated below and above the CQD film, respectively; the two layers are eventually removed, resulting in a single CQD film on an alien substrate. CQD films as large as 1 cm × 1 cm are transferred to any substrate, including flexible and prepatterned ones, with very little mechanical or optical damage. The wet‐transfer method can be repeated to form a CQD heterostructure. A CQD distributed feedback (DFB) laser is also demonstrated by transferring a thick CdSe‐based CQD layer (for both optical gain and waveguiding) on top of a surface grating structure. The resultant CQD structure exhibits a single‐mode DFB lasing action, with a high spontaneous emission factor (β ≈ 10 −3 ), owing to a strong vertical mode confinement and smooth surface morphologies on both sides of the CQD waveguide layer. Abstract : A transfer method for thick, densely packed colloidal quantum dot (CQD) films is developed. Releasing and supporting polymer layers dissolved in orthogonal solvents facilitate the transfer of fragile CQD films onto arbitrary, even structured substrates. Using the method, a CQD‐based freestanding distributed feedback laser is fabricated on a surface grating, and high‐quality single‐mode laser operation is observed.